A Grammatical Error Analysis Of Students’ Writing At SMAN Jogoroto In Academic Year Of 2022/2023 - Upi Lutfiyatul Khofifah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The objective of this study is to know the most frequent type of error made by the first grade students of SMAN Jogoroto in writing narrative and also the source of those errors. The writer used type of error of Betty Azar’s. The method used in this study was descriptive quantitative analysis method to describe students’ errors and analyze the data. The results of this study are from the data that has been collected by the The data that has been collected by the researcher is then described using Betty Azar's error classification which includes: singular-plural form, word form, word choice, verb form, word addition, word order, incomplete sentences, spelling, punctuation, capitalisation, article, unclear meaning, and non sequitur sentences. The researcher identified the errors found in the narrative texts written by students into three juvenile categories based on Betty Azar's classification. The researcher found that there were 13 grammatical errors that the researcher found in the students' written tests.